A troca de aniônios nos minerais argilosos - dos Santos, Aldo F (Revista Ceres, 1954)
The article is a review article on anion exchange in clay minerals. The main papers about the subject are revised. It is discussed the inlluences of free iron and aluminum oxides and some pretreatments to which clay minerals are submitted on the results of some anion exchange experiments. The author thinks there is enough evidence accumulated endorsing the recognition of anion exchange as a definite phenomenon in clay minerals. The data examined strongly indicates the hydroxyl groups in clay minerals as the site for anion exchange.